South African women as champions of change: A civil society programme of action for the African women’s decade - Chitiga-Mabugu M; Karuaihe S; Reddy V; Morison T; Botsis H; Ntuli M; Tsoanamatsie N (HSRC Press, 2014)
Women are agents of their own development and make valuable contributions towards the eradication of poverty and the establishment of early childhood structures in South Africa. South African Women as Champions of Change provides a perspective on the complexities in best practice case studies in respect of civil society engagement with poverty eradication, early childhood development, gender-based violence, and the advocacy initiatives aligned to some of these programs. A cross-cutting theme underpinning the analysis is an exploration of the socioeconomic conditions that promote employment creation for women. This book is a timely reminder of the invaluable contribution made by civil society organizations towards addressing the challenges affecting grassroots South African communities.
HSRC Press open access allows one free download per reader, but unlimited page viewing.